PERFORMANCE ASSESSMENT TO IMPROVE THE QUALITY OF PERFORMANCE AND SERVICE IN JAKARTA PPISHP FOOD SECURITY DEPARTMENT USING BALANCED SCORCARD - Retno Indriyati K; Franka Hendra; Jisman Hutasoit; Kurniawan Agung; Yuli Haryani (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
Center for Fisheries Production, Inspection and Certification (PPISHP) is a unit technical implementer within the Department of Food Security, Maritime Affairs and Agriculture of DKI Jakarta Province. PPISHP DKI Jakarta Province does not yet have a comprehensive performance measurement. Performance measurement only uses an assessment on the financial aspect, financial measures alone are not enough to evaluate the overall performance of the agency. Non-financial performance such as productivity and the ability of employees to produce products or services that can meet consumer desires is neglected. To measure the performance of an agency, a comprehensive performance measurement method is needed to achieve the desired goal. Therefore, the Balanced Scorecard method is deemed necessary to be applied to PPISHP DKI Jakarta Province.